EKSPRESI BONE MORPHOGENETIC PROTEIN (BMP) PADA 0-4 MINGGU PASCA FRAKTUR FEMUR DENGAN ATAU TANPA PENGGUNAAN BAHAN CANGKOK TULANG DEMINERALIZED FREEZ DRIED BOVINE BONE XENOGRAFT. - , agus purnomo, Dr. drh. Dhirgo Adji, M.P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fracture healing process is facilitated by the presence of growth factors in transplantation, especially Bone Morphogenetic Protein (BMP). This research aims to study the expression of Bone Morphogenetic Protein (BMP) in the healing process of rat femur fracture treatment with or without bone graft material and installation intrameduler pin. Twenty-four Sprague-Dawley male rats aged 2 months were divided into 3 groups randomly, each 8 rats. Rat group I are created 60% fracture, rats group II are made 100% fracture were fixed with intramedular pin and without graft material, rats group III are made 100% fracture were fixed intramedular pin and given a graft material. Twenty-four hours after surgery 2 rats selected from each group (total: 6 rats), blood taken for examination of total leukocytes and neutrophils, and rat was euthanased for retrieval of femur. The same treatment done in a row at one week, two weeks and four weeks post surgery. Femur were taken for histopathological examination and immunohistochemistry examination. Results of total leukocytes, neutrophils, histopathological and immunohistochemistry preparations were analyzed descriptively to see visible change in the organ by observation under a microscope. Overall results of this study indicate that the total leukocytes and neutrophils increased in the early phase of recovery and return to normal after 4 weeks post-surgery, Bone Morphogenetic Protein (BMP) expressed both at 24 hours, one week, two weeks, and four weeks post fracture and Demineralized Freeze-Dried Bovine bone xenograft (DFDBBX) is good and suitable materials used to treatment bone fracture.